SISTEM PENDUKUNG KEPUTUSAN DALAM PENENTUAN PADI BERKUALITAS MENGGUNAKAN METODE TOPSIS (STUDI KASUS: DESA WOROMARTO KEDIRI) - Rizky Firmansyah , Teguh; Mashuri , Chamdan (Inovate, 2023)
Selection of quality rice seeds affects rice yields in Indonesia, because rice is one of the staple foods of Indonesian citizens. The selection of quality rice can be done using the Topsis method. Researchers use the Topsis method because it can measure the relative performance of alternative decisions in a simple mathematical form to determine the quality of rice. With the TOPSIS method, the preference value of each alternative is calculated with predetermined criteria. The research was obtained through surveys and observations conducted in Woromarto Village. The results of the study state that the system developed provides recommendations for selecting the best rice effectively. Inpari 32 consistently gets the highest rating based on predetermined criteria, followed by Memberamo and Ciherang. This shows that Inpari 32 is the optimal choice for selecting high quality rice in Woromarto Village. System implementation has been tested and proven successful. Users can easily enter quality attribute data from each rice alternative into the system, and the system will generate recommendations based on a comparison of preference values. This application runs smoothly and meets the expected requirements. Keywords: Selection of Rice Seeds, Determination of Quality Rice, TOPSIS Method, Woromarto Village, Application Performance.